An investigation of restriction fragment length polymorphisms in the pro 2(1) collagen gene and their application to the analysis of inherited disorders of connective tissue - Brebner, D. K.(Diana Kirsty) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1985.